Gambaran Pemeriksaan Kadar Tes Toleransi Glukosa Oral (TTGO) pada Generasi Pertama Keluarga Penderita Diabetes Melitus - Waode Rustiah; A. Fatmawati Muharram; Dewi Arisanti; Tuty Widyanti; Nofi Sriyanti (Lontara Journal of Health Science and Technology, 2026)
Diabetes mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia, which occurs due to abnormalities in insulin secretion, insulin action, or both. Risk factors for diabetes mellitus include genetic factors and age. One of the initial diagnostic methods for blood glucose disorders is the oral glucose tolerance test (OGTT). The purpose of this study is to describe the results of OGTT in the first-generation family members of diabetes mellitus patients. This research is of an experimental laboratory nature, involving the administration of 75 grams of glucose to 10 family members, where one of their parents is a diabetes mellitus patient. Sample collection is done using the test strip method. The research findings show that out of the 10 first-generation family members of diabetes mellitus patients, one child experienced an increase in glucose levels after the administration of 75 grams of glucose, from 119 mg/dL to 204 mg/dL. Based on the criteria of the Indonesian Society of Endocrinology and Metabolism (PERKEMI), this child can be categorized as having diabetes mellitus. Furthermore, three other children are at risk of prediabetes due to having parents with a history of diabetes mellitus. The glucose levels of these three children increased after the administration of 75 grams of glucose, reaching 141 mg/dL (previously 117 mg/dL), 143 mg/dL (previously 104 mg/dL), and 131 mg/dL (previously 117 mg/dL), in accordance with PERKEMI criteria.